Why We Drop Out of School: Voices of San School Dropouts in Botswana - Mokibelo, Eureka B. (The Australian Journal of Indigenous Education, 2014)
Among San communities in Botswana, the rate of student disengagement from both primary and junior secondary school is an ongoing concern for educators. San learners leave school at all levels of primary and junior secondary education. Students who leave school have tended not to provide reasons as to why they are dropping out. This study investigated some of the reasons why San learners decided to drop out at primary and junior secondary school levels in the Central District in Botswana. In-depth interviews were undertaken with 20 former students living in five cattle-posts where the participants worked as cattle herders. The results indicate that some San drop out of school for reasons of survival, both within and outside school. The findings of the study offer insights into some of the issues that impede students within San communities in achieving their educational goals. Further, the findings could assist educational authorities in their review of current educational practices in Botswana so that that all citizens can be appropriately accommodated within the education system.